Crystal chemistry and electronic properties of the N=2 Ruddlesden-Popper manganates: Unconventional CMR materials - Battle, P; Blundell, S; Cox, D; Green, M; Millburn, J; Radaelli, P; Rosseinsky, M; Singleton, J; Spring, L; Vente, J (Materials Research Society, 1997)
The crystallography and electronic properties of the Ln(2-x)Sr(1+x)Mn(2)O(7) manganese oxides adopting the n = 2 Ruddlesden-Popper (RP) structure are discussed, focusing on the structural phase diagrams and electronic properties in the vicinity of the Mn + 3.5 oxidation slate and in particular the ease of synthesis of single phases of these materials.